Evaluation of a Child with Spells: A “Prefixed” Approach - Goraya, Jatinder S. (Journal of Pediatric Neurology, 2020)
Spells are a common clinical problem in children and can be broadly classified into epileptic and nonepileptic spells. Epileptic spells are clinical events that result from abnormal, excessive, and synchronous electrical activity of the cortical neurons. All other spells are included under the category of nonepileptic events. Precise differentiation between epileptic and nonepileptic spells, and their final characterization depend chiefly on obtaining a detailed account of the episode from the patient and/or witness. Physical and neurological examinations are generally non-revealing. In clinical practice, however, misdiagnosis of nonepileptic spells as epilepsy is fairly common and often is a result of incomplete history-taking. Explicit guidelines to elicit a thorough history in children who present with spells are lacking. The purpose of this article is to describe an instinctive and easy-to-remember approach to clinical history-taking in children with spells so as to minimize diagnostic errors.
Keywords: children; spells; epileptic; nonepileptic; approach